Chyluria in young child: a rare presentation. (16th March 2018) - Garg, Gaurav; Goel, Apul; Goel, Sunny; Singh, Manmeet
Abstract : Chyluria, a chronic manifestation of lymphatic filariasis, is rare in children. Clinicians must have a high index of suspicion to diagnose this condition in children as it mimics nephrotic syndrome. We present an unusual case in which a 7-year-old boy hailing from a filarial endemic region presented with a passage of milky urine, which on evaluation was diagnosed as parasitic chyluria. The child showed remission after medical management that persisted until 1 year of follow-up.